International comparisons of Poverty Intensity: Index Decomposition and Bootstrap Inference - Lars Osberg; Kuan Xu (Luxembourg Income Study (LIS), 1997)
This paper proposes an alternative formulation for the Sen-Shorrocks index of poverty intensity for survey data with sampling weights, and decomposes the Sen-Shorrocks index into the poverty rate, the average poverty gap ratio among the poor, and the overall Gini index of poverty gap ratios. This decomposition allows the percentage change in poverty intensity to be approximated as the sum of the percentage changes in the poverty rate and average poverty gap ratio. To account for sampling variation in estimates of poverty intensity, this paper also uses the bootstrap method to compute confidence intervals in international comparisons using Luxembourg Income Study data. Cross-sectional and longitudinal analyses indicate that in the early 1970's poverty intensity in Canada and the U.S. was almost indistinguishable, but in the 1970's Canadian poverty intensity decreased. Large increases in poverty intensity occurred in the 1980's in the United States, the United Kingdom, and Sweden.
Keywords: 330; Armut; Index; Welt